Economic costs of automated and continuous ambulatory peritoneal dialysis in Taiwan: a combined survey and retrospective cohort analysis. Issue 3 (21st March 2017) - Tang, Chao-Hsiun; Wu, Yu-Ting; Huang, Siao-Yuan; Chen, Hsi-Hsien; Wu, Ming-Ju; Hsu, Bang-Gee; Tsai, Jer-Chia; Chen, Tso-Hsiao; Sue, Yuh-Mou
Abstract : Objectives: Taiwan succeeded in raising the proportion of peritoneal dialysis (PD) usage after the National Health Insurance (NHI) payment scheme introduced financial incentives in 2005. This study aims to compare the economic costs between automated PD (APD) and continuous ambulatory PD (CAPD) modalities from a societal perspective. Design and setting: A retrospective cohort of patients receiving PD from the NHI Research Database was identified during 2004–2011. The 1:1 propensity score matched 1749 APD patients and 1749 CAPD patients who were analysed on their NHI-financed medical costs and utilisation. A multicentre study by face-to-face interviews on 117 APD and 129 CAPD patients from five hospitals located in four regions of Taiwan was further carried out to collect data on their out-of-pocket payments, productivity losses and quality of life with EuroQol-5D-5L. Outcome measures: The NHI-financed medical costs, out-of-pocket payments and productivity losses of APD and CAPD patients. Results: The total NHI-financed medical costs per patient-year after 5 years of follow-up were significantly higher with APD than CAPD (US$23 005 vs US$19 237; p<0.01). In terms of dialysis-related costs, APD had higher costs resulting from the use of APD machines (US$795) and APD sets (US$2913). Significantly lower productivity losses were found with APD (US$2619) than CAPD (US$6443), but the out-of-pocket payments were not significantly different. The differences in NHI-financed medical costs and productivity losses between APD and CAPD remained robust in the bootstrap analysis. The total economic costs of APD (US$30 401) were similar to those of CAPD (US$29 939), even after bootstrap analysis (APD, US$28 399; CAPD, US$27 960). No discernable differences were found in the results of mortality and quality of life between the APD and CAPD patients. Conclusions: APD had higher annual dialysis-related costs and lower annual productivity losses than CAPD, which made the economic costs of APD very close to those of CAPD in Taiwan.